2013
DOI: 10.1128/aem.02796-12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Broad-Spectrum Biofilm Inhibition by the Bacterium Bacillus sp. Strain SW9

Abstract: We isolated a Bacillus sp. strain that could display broad-spectrum biofilm inhibition. The broad biofilm prevention could be achieved mainly by direct contact between inhibitor and target cells or was accompanied by an interaction with secreted inhibitory compounds. The repression of cell surface fimbria-like appendages of a biofilm producer was also observed; this was considered to contribute to the reduction in mixed biofilms. Bacterial biofilm can cause enhanced risks of health threats and a multitude of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…strain SW9 that was capable of inhibiting biofilm formation in a wide range of bacteria. While, lipopeptide produced by Propionibacterium freudenreichii was known to inhibit Pseudomonas aeruginosa biofilm production (Wu et al 2013;Hajfarajollah et al 2014). The ability to inhibit biofilm formation is owned by Corixyn, the type of biosurfactant, produced by Corynebacterium xerosis strain NS.…”
Section: Discussionmentioning
confidence: 99%
“…strain SW9 that was capable of inhibiting biofilm formation in a wide range of bacteria. While, lipopeptide produced by Propionibacterium freudenreichii was known to inhibit Pseudomonas aeruginosa biofilm production (Wu et al 2013;Hajfarajollah et al 2014). The ability to inhibit biofilm formation is owned by Corixyn, the type of biosurfactant, produced by Corynebacterium xerosis strain NS.…”
Section: Discussionmentioning
confidence: 99%
“…Many earlier studies revealed that lipopeptide biosurfactants can be a useful approach to challenge microorganisms growing as a biofilm [67][68][69][70]. Dermatophytes grow in the form of a biofilm in vivo, making them difficult to remove surgically and resistant to traditional therapies [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, very few studies have reported antibiofilm compounds with broad-spectrum range [67,70,71]. However, despite of a long list of protein-and nonprotein-based antibiofilm agents discovered so far, there is no antibiofilm compound that is undergoing clinical or preclinical trials.…”
Section: • Lack Of Clinically Approved Antibiofilm Drugsmentioning
confidence: 94%